2016
DOI: 10.1002/2016jb013078
|View full text |Cite
|
Sign up to set email alerts
|

Rupture directivity of fluid‐induced microseismic events: Observations from an enhanced geothermal system

Abstract: The rupture process of fluid‐induced microseismic events is still poorly understood, mainly due to usually small magnitudes and sparse monitoring geometries. The high‐quality recordings of the earthquake sequence 2006–2007 at the enhanced geothermal system at Basel, Switzerland, constitute a rare exception, allowing a systematic directivity study of 195 events using the empirical Green's function method. We observe clear directivity signatures for about half the events which demonstrates that rupture directivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 58 publications
1
31
1
Order By: Relevance
“…More detailed modeling is to be preferred, but for many earthquakes of interest, the data are insufficient to resolve more complex sources. Folesky et al () found that the azimuthal variations in amplitude were less affected by filtering than the duration and so could also resolve orientation and rupture velocity. Their approach requires the same EGFs to be used at each station to preserve relative amplitude, limiting the input data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More detailed modeling is to be preferred, but for many earthquakes of interest, the data are insufficient to resolve more complex sources. Folesky et al () found that the azimuthal variations in amplitude were less affected by filtering than the duration and so could also resolve orientation and rupture velocity. Their approach requires the same EGFs to be used at each station to preserve relative amplitude, limiting the input data.…”
Section: Discussionmentioning
confidence: 99%
“…Lengliné and Got (), Kane et al (), and Wang, Rubin, and Ampuero () used azimuthal variation in spectral amplitudes to infer that the predominant rupture direction of earthquakes on the San Andreas Fault at Parkfield is consistent with the material contrast across the fault. Folesky et al () found that rupture direction within a cluster of fluid‐induced earthquakes depends on location and magnitude. There is still considerable uncertainty in the results of directivity studies due to lack of resolution of the data.…”
Section: Introductionmentioning
confidence: 99%
“…This is repeated station‐wise for the entire station network. We fit the amplitude variation model described by equation to the amplitudes obtained from the station‐wise reconstructed RSTFs in order to find the rupture direction of the event, that is, we solve for the parameters vrc and ϕ 0 (for more details, see Folesky et al, ). In the target area, the vast majority of events occur at the plate interface (Sippl et al, ) exhibiting similar thrust mechanisms (Cesca et al, ) with one fault plane oriented in good agreement with the dipping angle of the subducting slab.…”
Section: Methods and Testingmentioning
confidence: 99%
“…It is current understanding that rupture initiation, propagation, and termination are complex phenomena which are affected by multiple properties such as the material contrast of the juxtaposed rock types at the two sides of a fault (Ben‐Zion, ; Weertman, ). Also, among other aspects, stress state (e.g., Ampuero & Ben‐Zion, ) and perturbations of the stress field, for example, by pore pressure changes due to fluid injection, were proposed to affect rupture directivity (Folesky et al, ; Shapiro et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Still linked to shallow depth and near‐surface processes, Cesca et al [] found anomalous slow rupture of about 500 m/s for an induced earthquake, taking place along a weakened shallow subhorizontal failure plane, at the Ekofisk gas field, North Sea. Recently, Folesky et al [] studied the rupture directivity of fluid‐induced microseismic events and analyzed the induced seismicity sequence related to the EDS project in Basel (Switzerland). They found that the largest events of the sequence ( M l about 2) nucleate close to the pressure front and propagate backward into the stimulated volume, implying that maximum event size is related to dimension of the fluid‐perturbed volume [ Folesky et al , , ].…”
Section: Challenges In Discriminating Induced/triggered From Natural mentioning
confidence: 99%